1992
DOI: 10.1111/j.1365-2249.1992.tb03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory control values for CD4 and CD8 T lymphocytes. Implications for HIV-1 diagnosis

Abstract: SUMMARYWith the advent of standard flow cytometric methods using two-colour fluorescence on satnpies of whole blood, it is possible to establish the ranges of CD3, CD4 and CD8 T lymphocyte subsets in the routine laboratory, and also to assist the definition of HIV-l-re!ated deviations from these normal values. In 676 HIV-I-seronegative individuals the lymphocyte subset percentages and absolute counts were determined. The samples taken mostly in the morning. The groups included heterosexual controls, people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(98 citation statements)
references
References 50 publications
11
87
0
Order By: Relevance
“…Other studies have shown immune cell subset proportions in blood vary more between individuals than for the same individual over time [13,14], indicating a relatively stable phenotype. We sought novel biomarkers of such immunophenotypes using transcriptomics, and focusing on the 110 non-MHC MS susceptibility loci identified by GWAS.…”
Section: Introductionmentioning
confidence: 93%
“…Other studies have shown immune cell subset proportions in blood vary more between individuals than for the same individual over time [13,14], indicating a relatively stable phenotype. We sought novel biomarkers of such immunophenotypes using transcriptomics, and focusing on the 110 non-MHC MS susceptibility loci identified by GWAS.…”
Section: Introductionmentioning
confidence: 93%
“…The mean CD4 T cell count at start of HAART (baseline) was 688 cells/ l blood (range: 50 -2274) for children and 206 cells/ l blood (range: 19 -560) for adults. Because T cell counts per microliter of blood decrease with age and stabilize at the start of adolescence, total CD4 T cell counts, as well as counts of CD4 T cell subsets, were normalized for age-matched control values, which were derived from our cohort of healthy volunteers and were similar to values published by others (39,40). The mean normalized CD4 T cell number at the start of HAART was higher for children than for adults (39.5 and 25.7% of the age-matched control value, respectively).…”
Section: Recovery Of Cd4 T Cell Counts In Children and Adults Duringmentioning
confidence: 98%
“…In the absence of infection, the normal CD4 þ helper T-cell count averages 850 cells/mm 3 of peripheral blood, although it is known that there is a wide variance between individuals, with healthy values in adolescents and adults ranging from 500 cells/mm 3 to 1200 cells/mm 3 (Bofill et al, 1992).…”
Section: Parameter Values and Numerical Simulationsmentioning
confidence: 99%
“…Next, it is known that CTLs of a diverse range of specificities are continuously being produced. The average level of CD8 þ cytotoxic T-lymphocytes in a normal, healthy individual is roughly 550 cells/mm 3 of peripheral blood (Bofill et al, 1992). We will assume that at the start of infection, the number of circulating CD8 þ CTLs in an individual that can recognise HTLV-I epitopes is on the order of 10 À 1 cells/mm 3 .…”
mentioning
confidence: 99%